Polish as an Element of the Linguistic Landscape of the Specific Urban Space of Ostrava - Muryc, Jiří (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The subject of observation and subsequent analysis is primarily a static approach to examining the linguistic landscape (LL), focusing on public signs and spoken (audio) announcements in Polish recorded by the author in the form of photographs and audio recordings within the city of Ostrava, specifically at the Poruba Outdoor Swimming Pool. The author’s aim was to assess how language reflects the broader context of the development of ethnicity and current language dynamics. Therefore, a qualitative approach to the linguistic material was also of interest, with the goal of diagnosing, understanding and comparing indicators of LL in relation to several thematic areas – tourism, Czech merchants’ and service providers’ communication with customers in Polish and the LL in the city in general. The interest was also in the hierarchy of linguistic messages, their placement and whether they are monolingual, polyphonic or mixed.